The Circassian question: Russian colonial history in the Caucasus and a case of "Long-distance Nationalism" - Uwe Halbach (Stiftung Wissenschaft und Politik (SWP), 2014)
On 21 May 2014 Circassians all over the world marked the 150th anniversary of the expulsion of their ancestors from their North Caucasian homeland. The links between this unresolved legacy of Russian colonial history and President Putin's prestigious Winter Olympics in Sochi have reinvigorated Circassian activism. While different objectives and methods coexist within the movement, the demand for acknowledgement of the wrongs inflicted on their forebears is shared by both the remaining Circassian population in the North Caucasus and Russia (about 700,000) and the worldwide diaspora (several million). What challenges does this present for Russia? (SWP-Comments)
Keywords: 320